EXPRESSION OF CD4+, CD8+ LYMPHOCYTES IN BENIGN MENINGIOMAS - Тертишний, С.І. (World of Medicine and Biology, 2015)
The extent of CD4+, CD8+ expression in tumor-infiltrating lymphocytes was studied in benign meningiomas, obtained from patients undergoing neurosurgical craniotomies. We elucidated that benign meningiomas (meningothelial, transitional and fibrous subtypes) were characterized by evenly distributed CD4+, CD8+ tumor-infiltrating lymphocytes with increase of their density around microvessels. Quantity of CD8+ lymphocytes exceeded number of CD4+ lymphocytes in 2,81-3,21 times. The ratio of CD4 + / CD8 + T-lymphocytes was 0,3-0,35. Along with extensive CD4+ and CD8+ expression in tumor-infiltrating lymphocytes weak expression of CD4+ and CD8+ was registered, which can normally be found in monocytes, tissue macrophages and NK-cells. This data prove broad distribution of immune cells in meningiomas and needs further investigation.
Keywords: CD4+; CD8+ lymphocytes; benign meningiomas